The Relationship between Job Stress and Employees’ Innovation Behavior - Wu, Qingqing (International Journal of Social Sciences and Public Administration, 2025)
With the fierce market competition, employees’ innovative behavior is crucial for organizations to maintain competitiveness. Targeting Chinese corporate employees, this study aims to reveal how job characteristics (including demands and resources) influence employee innovation behavior through challenging and hindering job stress. The empirical research is based on questionnaire survey data. 517 enterprise employees in China were investigated with the Job Requirements-Resources Scale, Challenge-Hindrance Stress Scale, and Innovation Behavior Scale. Results show that: (1) Job demands, challenging stress, and job resources differ significantly by gender (males > females); analysis found that job requirements show a specific trend with age: employees aged 29-39 have the highest job requirements, followed by employees aged 18-28, and both are significantly higher than those aged 40-50 and above; innovative behavior is higher in private enterprises than in state-owned enterprises. (2) Correlation analysis results indicate significant positive correlations among the variables studied. Specifically:Job demands are not only positively correlated with job resources, but also with challenging stress and innovative behavior; Job resources are significantly positively correlated with challenging stress and innovative behavior;Furthermore, challenging stress has also been shown to be significantly positively correlated with innovative behavior.(3) The study shows that challenging stress mediates the impact of job demands on innovative behavior, and job resources moderate the relationship between job demands and challenging stress. This conclusion has guiding value for Chinese organizations to improve employee innovation through job design optimization.